'Churchill rolled the tanks into the crowd': mythology and reality in the military deployment to Glasgow in 1919. Issue 1 (February 2019) - Barclay, Gordon J.
Abstract : The 'Battle of George Square', 31 January 1919, is perhaps the most mythologised event in 20th-century Scottish history. A demonstration in support of the 40-hours strike descended into a violent riot and the Sheriff of Lanarkshire read the Riot Act and called in military aid, which he had already made sure would be available. Ten thousand, mainly Scottish, troops arrived that night in a city that was already returning to peace, followed three days later by six tanks. A largely mythological version of events has dominated Scottish popular history during the last century and the mythology has more recently developed beyond a narrative of 'capitalist oppression' to include one of 'English oppression', the deployment of 'English troops', by an 'English government', 'sent by Churchill'. This paper attempts to document the formation of the different elements of the mythology (while briefly explain why they are myths), how they have developed and been used in popular history and more recently, in political discourse on social media.